Wheat (Triticum aestivum L.)‐based intercropping systems for biological pest control. Issue 12 (15th July 2016) - Lopes, Thomas; Hatt, Séverin; Xu, Qinxuan; Chen, Julian; Liu, Yong; Francis, Frédéric
Abstract: Wheat ( Triticum aestivum L.) is one of the most cultivated crops in temperate climates. As its pests are mainly controlled with insecticides that are harmful to the environment and human health, alternative practices such as intercropping have been studied for their potential to promote biological control. Based on the published literature, this study aimed to review the effect of wheat‐based intercropping systems on insect pests and their natural enemies. Fifty original research papers were obtained from a systematic search of the peer‐reviewed literature. Results from a vote‐counting analysis indicated that, in the majority of studies, pest abundance was significantly reduced in intercropping systems compared with pure stands. However, the occurrence of their natural enemies as well as predation and parasitism rates were not significantly increased. The country where the studies took place, the type of intercropping and the crop that was studied in the association had significant effects on these results. These findings show that intercropping is a viable practice to reduce insecticide use in wheat production systems. Nevertheless, other practices could be combined with intercropping to favour natural enemies and enhance pest control. © 2016 Society of Chemical Industry